Pengabdian Kepada Masyarakat Melalui Kuliah Kerja Nyata (KKN) di Desa Buni Bakti Kabupaten Bekasi - Fadli Muhammad Athalarik; Rosa Auliya Ananda; Zakiah Husni Rohmadina; Arul Ardiansyah Lisandi; Annisa Sabrina; Dinda Devita Cahyani; Dwi Laras Lestari; Abror Ahmad Mubaraq; Muhammad Rayyan Attala; Raihan Aditia Rahayu; Verdita Febryana; Kelvin Kurniadiningrat Madisa; Sayipul Arba; Caroline Nathania Simamora; Muhammad Rubby Syahdan (Yayasan Daarul Huda Kruengmane, 2026)
Community Service through Real Work Lectures (KKN) of Universitas Bhayangkara Jakarta Raya was conducted in RT 002 RW 002 Kampung Kerangkeng, Buni Bakti Village, Babelan District, Bekasi Regency from May to June 2026. The program aimed to address several community issues, including low financial literacy among children, limited flood preparedness, low environmental awareness, and inadequate neighborhood identification facilities. The methods employed included observation, coordination, program implementation, and evaluation. The activities consisted of the ASA Movement (Children Aware of Saving), Basic Rescue and Flood First Aid Training in collaboration with BASARNAS, the GERAK Program (Active Community Movement) for a Clean and Healthy Environment, and the installation of neighborhood identification signs. The results indicated an improvement in children's understanding of the importance of saving, increased community knowledge regarding flood preparedness, greater awareness of environmental cleanliness, and the availability of neighborhood identification signs that facilitated area recognition. Overall, the program contributed to enhancing community knowledge, participation, and awareness while supporting a more orderly and sustainable environment.